The permeability of virtual macroporous structures generated by sphere packing models: comparison with analytical models - Otaru, A.J.; Kennedy, Andrew R. (Elsevier, 2016)
Realistic porous structures typical of those made by replication of packed beds of spherical particles have been produced by a novel modelling method. Fluid dynamics simulation of the permeability of these structures agrees well with experimental measurements and similar modelling of structures derived from X-ray tomographic images. By varying the model structures the “bottleneck” flow concept proposed by analytical models in the literature was substantiated, confirming the high dependence of permeability on the size of the windows connecting the pores but also highlighting the need for accurate determination of the connectivity of the pores for these models to be accurate.